INDEPENDENCE OF JUDICIAL AND PROSECUTION SYSTEM IN KOSOVO - Besim Kelmendi (European Scientific Journal, ESJ, 2015)
Independence of judicial and prosecution system in Kosovo has had a very interesting development and maybe unseen till now, in any country in the European Union or broader. This is because since 1999, the United Nations Mission was deployed in Kosovo which was running the three powers, the legislative, executive and the judicial system and it had the absolute influence in all matters related to functioning of courts and prosecutions in Kosovo, beginning from their establishment to determining the number of judges and prosecutors, their appointment, salaries, their work conditions and buildings where they worked. Following the declaration of independence of Kosovo in February 2008, Kosovo has undertaken some steps towards independence of judicial and prosecution system from the executive and legislative powers, but not yet in the appropriate level and in harmony with international standards, therefore, in this paper there will be some challenges related to independence of judicial and prosecution system to be discussed, based on constitutional and legal provisions of Kosovo and comparing them with international provisions or documents which have tackled this topic. This paper shall briefly present the role of Government and institutions under its directives, the role of the Assembly and the role of Presidency in independence of judicial and prosecution system and for the internal independence of this system itself. Through this paper, the author is going to try to give answer to ten questions which are related to independence of judicial and prosecution system in Kosovo, trying to recover these answers from the powers of executive and legislative power in relation to judicial system.